The reality of human resources and scientific research at Tishreen University and its impact on sustainable development - محمود, نيرمين (Latakia University Journal -Biological Sciences Series, 2024)
The research aimed to study the characteristics of human resources and the scientific research environment at Tishreen University and their role in achieving sustainable development goals. To achieve the objectives of the research, a questionnaire was designed and distributed to a random sample of faculty members in the university's faculties, consisting of (100) members, including a teacher, an assistant professor, and a professor. The research adopted the descriptive analytical method in its survey style in describing the characteristics of the sample and analyzing its responses to the axes of the questionnaire using the SPSS 20 program. The results of the research showed that the university is rich in its well-qualified human cadres, and that the research environment has an average level in terms of the purpose for which it was designed, in contrast to the presence of a low level of funding for scientific research, as it came with a low degree of approval. The results also showed that there are statistically significant differences in the respondents' answers about human resources and their role in achieving sustainable development due to the scientific rank of the faculty member, in addition to the existence of a statistically significant relationship between the reality of scientific research and the role of the university in achieving sustainable development. The research recommended the need to modernize the scientific research environment of equipment, laboratories and communication devices that would enhance the role of the university in achieving sustainable human development for its cadres, and to provide incentive rewards to faculty members according to the research submitted by each member, which in turn contributes to raising the scientific level for them.